Globalization and Non-Traditional Security Challenges in Developing Countries: The Indonesian Case - Shelvia Arnie Putri; Timbul Dompak; Lubna Salsabila; Etika Khairina (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This research examines the impact of globalization on non-traditional security in Indonesia. Using a literature study approach, the research collects secondary data from various sources, including scientific journals, government reports, and publications from international institutions. Globalization has introduced several new challenges to Indonesia's non-traditional security, such as terrorism, transnational crime, environmental degradation, food and energy security, and cyber threats. This study explores different dimensions of non-traditional security risks, evaluates the effectiveness of current policy responses, and identifies potential strategies to strengthen Indonesia's national resilience in addressing contemporary security challenges. The research finds that globalization accelerates cross-border mobility, enhances extremist groups' access to the internet, and intensifies environmental damage. In response, the Indonesian government has implemented measures such as strengthening anti-terrorism laws, promoting deradicalization programs, enhancing border controls, fostering ASEAN regional cooperation, imposing a moratorium on land clearing, and supporting the REDD+ program. However, challenges remain, including limited resources, coordination issues between institutions, and low levels of digital literacy among the public, which hinder progress in improving non-traditional security in Indonesia.